Influence of the Surgical Education and Training programme on the Fellowship Examination. Issue 6 (30th April 2013) - Beasley, Spencer W.; Hardware, Narelle
Abstract Introduction of an increasingly competence‐based Royal Australasian College of Surgeons (RACS) Surgical Education and Training (SET) programme has influenced the nature and conduct of the Fellowship Examination (FEX). The FEX is the final summative assessment taken near the completion of SET training, and is aligned to the other SET assessment processes. It mainly tests two of the nine RACS surgical competencies, focusing on professional judgement and the clinical application of knowledge. It is used to help determine whether candidates are safe to practise unsupervised at consultant level. There have been refinements to a number of the processes including standard setting, blueprinting, developing marking descriptors and improving the reliability and validity of the examination. An Examiners' Training Course has also been introduced.